2011
DOI: 10.1007/s00345-011-0767-z
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase expression profile in clear cell renal cell carcinoma

Abstract: TK constitute valuable targets for pharmaceutical anti-cancer therapy. ERBB4 and HCK depict significantly lower expression levels in renal cancer tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
2
25
0
Order By: Relevance
“…Thus, we propose that PTK7 IHC staining grade could be used as a prospective prognostic determinant of ESCC. Although previous studies have reported a decrease in PTK7 expression levels in metastatic melanoma (25) and clear cell renal cell carcinoma, (26) PTK7 has been shown to be upregulated in many types of human malignancy, including colon cancer, lung carcinoma, liposarcoma, gastric cancer, and acute myeloid leukemia. (11,(17)(18)(19)(20)22) Prebet et al (20) reported that increased expression of PTK7 is correlated with poor clinical outcome in acute myeloid leukemia, a finding that was linked to increased cell migration and resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus, we propose that PTK7 IHC staining grade could be used as a prospective prognostic determinant of ESCC. Although previous studies have reported a decrease in PTK7 expression levels in metastatic melanoma (25) and clear cell renal cell carcinoma, (26) PTK7 has been shown to be upregulated in many types of human malignancy, including colon cancer, lung carcinoma, liposarcoma, gastric cancer, and acute myeloid leukemia. (11,(17)(18)(19)(20)22) Prebet et al (20) reported that increased expression of PTK7 is correlated with poor clinical outcome in acute myeloid leukemia, a finding that was linked to increased cell migration and resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 95%
“…(24) However, PTK7 expression has been shown to be decreased in metastatic melanoma (25) and clear cell renal cell carcinoma. (26) In addition, chromosome 6p, (27) on which the PTK7 gene is located, was found to be deleted in breast carcinoma (28) and malignant melanoma. (29) Although the role of PTK7 in different cancers has not been studied comprehensively, PTK7 is likely to have a tumorpromoting role in general.…”
mentioning
confidence: 99%
“…In recent years, activation of ABL1 and ABL2 has been detected in solid tumors, including breast, colon, lung, and kidney carcinoma, as well as melanoma 7-16 . Activation of ABL kinases in solid tumors is not linked to chromosome translocation events, but rather is driven by enhanced ABL1 or ABL2 expression and/or by oncogenic tyrosine kinases, chemokine receptors, oxidative stress, and/or inactivation of negative regulatory proteins (cbioportal.org; 3, 16-21 ). Here we compare the modes of ABL family kinase activation in leukemias and solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Other members of this signaling network have been characterized to play a pro-inflammatory role in ccRCC. These include SCD1 (stearoyl-CoA desaturase 1) [24], BTK (bruton agammaglobulinemia tyrosine kinase) [25, 26], and FXYD5 (FXYD domain containing ion transport regulator 5, dysadherin) [27-29]. CDH13 appears to be frequently methylated in cancer, however its expression has been reported to be upregulated in tumor-associated vasculature, where it promotes endothelial cell proliferation and migration [30].…”
Section: Resultsmentioning
confidence: 99%